Priority areas for conservation of Old World vultures. Issue 5 (13th March 2019) - Santangeli, Andrea; Girardello, Marco; Buechley, Evan; Botha, Andre; Minin, Enrico Di; Moilanen, Atte
Abstract: The prosperity and well‐being of human societies relies on healthy ecosystems and the services they provide. However, the biodiversity crisis is undermining ecosystems services and functions. Vultures are among the most imperiled taxonomic groups on Earth, yet they have a fundamental ecosystem function. These obligate scavengers rapidly consume large amounts of carrion and human waste, a service that may aid in both disease prevention and control of mammalian scavengers, including feral dogs, which in turn threaten humans. We combined information about the distribution of all 15 vulture species found in Europe, Asia, and Africa with their threats and used detailed expert knowledge on threat intensity to prioritize critical areas for conserving vultures in Africa and Eurasia. Threats we identified included poisoning, mortality due to collision with wind energy infrastructures, and other anthropogenic activities related to human land use and influence. Areas important for vulture conservation were concentrated in southern and eastern Africa, South Asia, and the Iberian Peninsula, and over 80% of these areas were unprotected. Some vulture species required larger areas for protection than others. Finally, countries that had the largest share of all identified important priority areas for vulture conservation were those with the largest expenditures related to rabies burden (e.g., India, China, and Myanmar). Vulture populations have declined markedly in most of these countries. Restoring healthy vulture populations through targeted actions in the priority areas we identified may help restore the ecosystem services vultures provide, including sanitation and potentially prevention of diseases, such as rabies, a heavy burden afflicting fragile societies. Our findings may guide stakeholders to prioritize actions where they are needed most in order to achieve international goals for biodiversity conservation and sustainable development. Abstract : Article impact statement : Eighty percent of areas important for Old World vulture conservation are unprotected and in southern and eastern Africa, South Asia, and Iberia. Abstract : Áreas Prioritarias para la Conservación de Buitres del Viejo Mundo Resumen: La prosperidad y el bienestar de la sociedad humana dependen de ecosistemas sanos y de los servicios ambientales que éstos proporcionan. Sin embargo, la crisis de biodiversidad está afectando a los servicios ambientales y sus funciones. Los buitres se encuentran entre los grupos taxonómicos con mayor amenaza sobre el planeta, a pesar de tener una función fundamental en los ecosistemas. Estos carroñeros obligados consumen rápidamente grandes cantidades de carroña y desechos humanos, un servicio que puede ayudar en la prevención de enfermedades y en el control de mamíferos carroñeros, incluyendo a los perros ferales, los cuales pueden ser un peligro para los humanos. Combinamos la información sobre la distribución de las 15 especies de buitres en Europa, Asia y África con las amenazas que presentan y usamos el conocimiento detallado de expertos sobre la intensidad de las amenazas para priorizar las áreas críticas para la conservación de buitres en África y en Eurasia. Las amenazas que identificamos incluyeron el envenenamiento, la mortalidad por colisiones con infraestructura eólica y otras actividades antropogénicas relacionadas con el uso de suelo y la influencia humana. Las áreas importantes para la conservación de buitres estuvieron concentradas en el sur y el este de África, el sur de Asia y la Península Ibérica, y más del 80% de estas áreas no contaban con protección. Algunas especies de buitres requirieron áreas más grandes para su protección que otras especies. Finalmente, los países que tuvieron la mayor porción de todas las áreas prioritarias importantes e identificadas para la conservación de buitres también fueron aquellos con los mayores gastos relacionados con la carga de la rabia (por ejemplo, India, China y Myanmar). Las poblaciones de buitres han declinado marcadamente en la mayoría de estos países. La restauración de poblaciones sanas de buitres por medio de acciones enfocadas en las áreas prioritarias que identificamos puede ayudar a restaurar los servicios ambientales que proporcionan los buitres, incluyendo el saneamiento y la prevención potencial de enfermedades, como la rabia, una carga pesada que aflige a las sociedades frágiles. Nuestros resultados pueden guiar a los interesados hacia la priorización de acciones en donde más se necesitan para poder alcanzar los objetivos internacionales para la conservación de la biodiversidad y el desarrollo sustentable. 摘要: 人类社会的繁荣昌盛依赖于健康的生态系统及其所提供的服务。然而, 生物多样性危机正在破坏生态系统的服务和功能。秃鹰是地球上最濒危的类群之一, 而它们却能提供基础的生态系统功能。它们作为专性食腐动物可以快速消耗大量腐肉及人类废弃物, 提供的生态系统服务有助于预防疾病, 以及控制哺乳类食腐动物, 如会对人类造成威胁的野狗。我们将欧洲、亚洲和非洲的全部十五种秃鹰的分布信息与其面临的威胁相结合, 利用详细的关于威胁强度的专业知识, 确定了非洲及欧亚关键的秃鹰保护优先地区。秃鹰面临的威胁包括中毒、撞击风能设施导致的死亡, 以及与人类土地利用和影响有关的其它人类活动。秃鹰的重点保护区域集中在非洲南部和东部、南非和利比亚半岛, 这些地区超过 80% 的土地没有得到保护。另外, 秃鹰中某些物种相比之下需要更大区域进行保护。我们还发现, 秃鹰的重要优先保护区域占比最大的国家同时也是那些在狂犬病上的支出最高的国家（如印度、中国、缅甸）, 而其中大多数国家的秃鹰种群数量已经明显下降。通过在我们确定的优先保护区域采取有针对性的行动来恢复健康的秃鹰种群, 可能有助于恢复秃鹰提供的生态系统服务, 包括环境卫生和预防潜在疾病, 比如狂犬病这种沉重的社会负担。我们的研究成果可以指导利益相关者在需求最迫切的地方优先采取行动, 以实现生物多样性保护和可持续发展的国际目标。【翻译: 胡怡思; 审校: 聂永刚】